Efficacy of Dexpanthenol, Olive Oil and Breast Milkfor the Nipple Crack Treatment in Lactating Mothers - Noreen Kousar, Muhammad Tariq Ghaffor, Sadaf Shahzadi, Sohail Sabir, Sajida Naseem, Syeda Sabahat Haider, (Pakistan Journal of Medical & Health Sciences, 2022)
Cracked nipple is a painful condition for lactating mothers and if untreated leads to lactational mastitis, breast abscesses Objectives: T o compare the efficacy of dexpanthenol, olive oil and breast milk for nipple cracks treatment in lactating mothers Outcome Measures: We measured the Severity of pain (the primary outcome) by using visual analogue scale (VAS) and healing of cracked nipple (Secondary outcome) was assess by Nipple trauma score (NTS) before treatment and after7days, 14 days of treatment Material And Methods: We conducted a quasi experimental study from march 2022 to end of august 2022 in sheikh zayed hospital, Rahim Yar Khan after ethical approval from institutional review board. The total numbers of 120patient were equally divided into three groups using Breast milk, Olive oil or Dexpanthenol respectively for their cracked nipples. The data was collected on predesigned Performa.Data Analysis Procedure: We measured the percentages ,means and standard deviations with the help of statistical package for social sciences version (SPSS) version 28. ANOVA test and Non-parametric test were also used to test the difference between study groups Results: At day0 baseline mean nipple pain score and nipple trauma score was same in all groups.At day 7 breast milk and olive oil show better reduction in pain as compared to Dexpanthenol.At day 14 olive oil showed statistically significant reduction in pain as compared to breast milk and dexpanthenol t. At day 7 and day 14 olive oil show statistically significant better healing of cracked nipples as compared to Breast milk and Dexpanthenol. Practical implication Conclusion: Our study is proving that olive oil is better than Breast milk and Dexpanthenol in term of pain relief and healing of cracked nipples proving hypothesis: H2 Keywords: Cracked nipple, olive oil, Breast milk, Dexpanthenol.